Cyanobacteria in soils under dryland agricultural production systems = Cianobacterias en suelos bajo sistemas de producción agrícola en secano - Sánchez, Cecilia Isabel; Gregorutti, Viviana Carolina (Elsevier, 2025)
Algae and cyanobacteria are photoautotrophic organisms, which develop in the first centimeters of soil7 and are a primary source of carbon (C) and nitrogen (N) for heterotrophic soil-dwelling microorganisms6. The aim of this study was to characterize the cyanobacteria inhabiting agricultural soils under two managements: sustainable intensification management (SIM) and transition to agroecology management (TAM).